The International Criminal Court and Catholic Social Doctrine - John M. Czarnetzky (Chrześcijaństwo-Świat-Polityka)
The International Criminal Court was the result of decades of postwar pressure to establish a permanent tribunal with jurisdiction over the most heinous crimes against humanity.  Despite the noble goals of its architects, the ICC has not been effective in prosecuting such crimes.  The author argues that the reasons for the Court’s ineffectiveness were apparent from its inception due to the flawed view of the human person and society that is at the foundation of the Court.  Using the insights of Catholic Social Doctrine, this article dissects the erroneous social anthropology, which is the basis for the Court’s design, and suggests possible correctives based on a correct understanding of the human person and human society.